Consumer Religiosity Based on Islamic Perspective: Comparison between Muslim Students at Public University and Islamic University in Pekanbaru City - Julina Julina (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aims to determine whether there are differences in the level of religiositybetween students from public universities and Islamic universities. Religiosity is animportant aspect to be examined in the field of consumer behavior considering religion isthe most fundamental cultural factor that influences consumer choice of products andservices. Religiosity in this study refers to research by Khraim (2010) which is measuredusing four dimensions that is religious education, financial services, current issues, andproducts with sensitive elements. Respondents are students of two state universities inPekanbaru City. Data is collected using questioner and then analyzed by usingindependent sample t test. The results showed no significant differences betweenrespondents who came from public universitiy and Islamic university. Pekanbaru city isinhabited by the majority of Muslims make the level of religiosity of students is not showdifferences even though the Islamic university curriculum contains more elements ofIslamic education. The results of this study can be a reference for marketers to set targetmarketing to Muslim consumers in general in Pekanbaru City.Keywords: Islamic University; Public University; Religiosity